Land Resources Evaluation for Damage Compensation to Indigenous Peoples in the Arctic (Case-Study of Anabar Region in Yakutia) - Sergey I. Nosov; Boris E. Bondarev; Andrey A. Gladkov; Violetta Gassiy (Resources, 2019)
The compensation for losses caused to the indigenous peoples in Arctic Russia due to the industrial development of their traditional lands is an urgent question whose resolution requires development of new mechanisms and tools. The losses caused to indigenous traditional lands are part of the damage caused to the natural environment, their culture and livelihood. In the Russian Federation cultural impact assessment is a rather new tool aiming to protect indigenous peoples’ rights to lands. In this paper the authors show the applied side of the cultural assessment that is used to improve the methodology of the calculation of losses adopted by ministry of regional development in Russia in 2009. This methodology is based on the resource disposition and evaluation of traditional lands. Accordingly, compensation payments are calculated as the sum of the losses in traditional economic activities such as: reindeer herding, hunting, fishing and gathering. Such compensation is considered by authors as the elements of a benefit-sharing system. In practice, this methodology has been tested at industrial projects on alluvial diamonds in Yakutia. In this paper we look at the Polovinnya project case-study which deals with indigenous peoples of Dolgans and Evenks and argues that such a justified, understandable methodology both for indigenous peoples and subsoil user could reduce to a minimum the conflict of interests.